Role of Denver II and Development Quotients in the management of several pediatric developmental and behavioral disorders - Titi Sularyo; Bernie Endyarni; Tri Lestari H; Tirza Z. Tamin; Gitayanti Gitayanti (Paediatrica Indonesiana, 2012)
Background Autism spectrum disorder (ASD) and attention deficitand hyperactivity disorder (ADHD) are nowadays becoming moreand more frequently found. Parents are worried of the possibilitythat their children suffer from them. Growth and developmentclinics (GDC) should be able to deliver professional services. Thusa practica~ applicable, objective, valid, reliable, and able to measuredevelopment quotient (DQ) values instrument is needed.Objective To find out whether the Denver II instrument andDQ values can be used in the management of children with ASDandADHD.Methods A study was carried out on cases of children withASD, multisystem development disorder (MSDD), pervasivedevelopment disorder - n ot otherwise specified (PDD-NOS), andattention deficit and hyperactivity disorder (ADHD), consistingof history taking, physical examination, establishing diagnosis,therapy, evaluation, and follow-up. The Denver II instrumentwas used and DQ values in all development streams established.The study was done at the GDC of Hermina Depok Hospital inJuly 2008 - June 2009.Results It revealed that results of the Denver II as seen on thefilled Denver II form showed "typical" features related to kind ofdisorder as far as category ofDQ value, dissociation, global delayeddevelopment (GDD) as well as abnormality of the test behaviorwere concerned. It also revealed that establishing the diagnosesby the use of the Denver II and DQ values gave exactly the samediagnoses as when using the conventional way by the expert.Conclusion The Denver II instrument with DQ values can beused in the management of ASD and ADHD cases. [Paediatrlndones. 2012;52:51-6].